Pelatihan Programmable Logic Controller untuk Meningkatkan Kompetensi Siswa Di SMKN 1 Masbagik - Ahmad, Ramli; Taufik Akbar; M. Nuzuluddin; Ahwan Ahmadi; Intan Komala Dewi (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
Programmable Logic Controllers (PLCs) play a significant role in enhancing student competency in the field of education, particularly in rural regions. This research seeks to enhance the proficiency of SMKN 1 Masbagik students in operating PLCs through rigorous training focused on practical application. The training program spanned six days and involved 35 students, utilizing participatory methods and incremental assessment. The offered content encompasses Introduction to PLC, Types of PLC, PLC and Wiring Hardware, PLC Programming, Basic Applications, Intermediate Applications, HMI (Human Machine Interface), PLC Communication, and Troubleshooting. The assessment by pre-test and post-test indicated an enhancement in average scores from 45 to 85 percent. The students had a favorable response and commended the employed interactive tactics. The training outcomes demonstrate that the practice-based approach significantly enhances student competence at SMKN 1 Masbagik. This program aims to serve as a model for other schools to adopt analogous training, so enhancing students' preparedness for the difficulties of the digital age and the progressively competitive landscape of employment and education